Involvement of placental/umbilical cord blood acid–base status and gas values on the radiosensitivity of human fetal/neonatal hematopoietic stem/progenitor cells - Yamaguchi, Masaru (Oxford University Press, 2013)
Arterial cord blood (CB) acid–base status and gas values, such as pH, PCO(2), PO(2), HCO(3)(−)and base excess, provide useful information on the fetal and neonatal condition. However, it remains unknown whether these values affect the radiosensitivity of fetal/neonatal hematopoiesis. The present study evaluated the relationship between arterial CB acid–base status, gas values, and the radiosensitivity of CB hematopoietic stem/progenitor cells (HSPCs). A total of 25 CB units were collected. The arterial CB acid–base status and gas values were measured within 30 min of delivery. The CD34(+)HSPCs obtained from CB were exposed to 2 Gy X-irradiation, and then assayed for colony-forming unit-granulocyte-macrophage, burst-forming unit-erythroid (BFU-E), and colony-forming unit-granulocyte erythroid, macrophage and megakaryocyte cells. Acid–base status and gas values for PCO(2)and HCO(3)(−)showed a statistically significant negative correlation with the surviving fraction of BFU-E. In addition, a significant positive correlation was observed between gestational age and PCO(2). Moreover, the surviving fraction of BFU-E showed a significant negative correlation with gestational age. Thus, HSPCs obtained from CB with high PCO(2)/HCO(3)(−)levels were sensitive to X-irradiation, which suggests that the status of arterial PCO(2)/HCO(3)(−)influences the radiosensitivity of fetal/neonatal hematopoiesis, especially erythropoiesis.